The Influence of Knowledge Management Capability Dimensions on the Competitive Advantage of MSMEs Through Entrepreneurial Orientation - Erwin Permana; Khalida Utami; Margo Purnomo (Jurnal Manajemen Teknologi, 2023)
Abstract. The concept of knowledge management as the mainstay for building the competitive advantage of large companies has been highly emphasized in the strategic management literature, but similar studies are still rare in the realm of MSMEs. To fill this gap, this paper empirically examines the relationship between the dimensions of knowledge management capability and competitive advantage through the entrepreneurial orientation of Micro, Small and Medium Enterprises (MSMEs). The knowledge management dimensions used include knowledge management infrastructure and knowledge management processes. The analysis technique uses Structural Equation Model (SEM) with SmartPLS. Research respondents are owners/managers in 75 MSME sentra in Jakarta, Indonesia. Statistical tests show that knowledge management infrastructure has a significant effect on entrepreneurial orientation but does not have a significant effect on competitive advantage. The knowledge management process has a significant effect on entrepreneurial orientation and also on competitive advantage. Meanwhile, entrepreneurial orientation has a significant effect on competitive advantage. This reality confirms that when there is high pressure on MSMEs, it will cause actions and reactions among companies in the industry. To emphasize the important role of knowledge management in facing future pressures, wider research is needed on the consequent variables of the application of knowledge management in MSMEs, such as digital capabilities, business agility and business performance.Keywords: Knowledge management infrastructure, knowledge management processes, competitive advantage, entrepreneurial orientation, MSMEAbstrak. Konsep knowledge management sebagai andalan untuk membangun keunggulan kompetitif perusahaan besar sudah sangat ditekankan dalam literatur strategic management, namun studi serupa masih jarang dilakukan di ranah UMKM. Untuk mengisi kesenjangan tersebut, makalah ini mengkaji secara empiris hubungan antara dimensi kapabilitas manajemen pengetahuan dan keunggulan kompetitif melalui orientasi kewirausahaan Usaha Mikro, Kecil dan Menengah (UMKM). Dimensi manajemen pengetahuan yang digunakan meliputi infrastruktur manajemen pengetahuan dan proses manajemen pengetahuan. Teknik analisis menggunakan Structural Equation Model (SEM) dengan SmartPLS. Responden penelitian adalah pemilik/pengelola di 75 sentra UMKM di Jakarta, Indonesia. Uji statistik menunjukkan bahwa knowledge management infrastructure berpengaruh signifikan terhadap orientasi kewirausahaan namun tidak berpengaruh signifikan terhadap keunggulan kompetitif. Proses knowledge management berpengaruh signifikan terhadap orientasi kewirausahaan dan juga keunggulan bersaing. Sedangkan orientasi kewirausahaan berpengaruh signifikan terhadap keunggulan bersaing. Realitas ini menegaskan bahwa ketika terjadi tekanan yang tinggi terhadap UMKM akan menimbulkan aksi dan reaksi antar perusahaan dalam industri tersebut. Untuk menekankan peran penting knowledge management dalam menghadapi tekanan masa depan, diperlukan penelitian yang lebih luas terhadap variabel-variabel konsekuen penerapan knowledge management pada UMKM, seperti kapabilitas digital, business agility dan business performance.Keywords: Knowledge management infrastructure, knowledge management processes, competitive advantage, entrepreneurial orientation, MSME